Population-based study demonstrating an increase in colorectal cancer in young patients. Issue 8 (5th April 2017) - Gandhi, J; Davidson, C; Hall, C; Pearson, J; Eglinton, T; Wakeman, C; Frizelle, F
Abstract: Background: New Zealand has among the highest rates of colorectal cancer in the world and is an unscreened population. The aim of this study was to determine the trends in incidence and tumour location in the New Zealand population before the introduction of national colorectal cancer screening. Methods: Data were obtained from the national cancer registry and linked to population data from 1995 to 2012. Incidence rates for colorectal cancer by sex, age (less than 50 years, 50–79 years, 80 years or more) and location (proximal colon, distal colon and rectum) were assessed by linear regression. Results: Among patients aged under 50 years, the incidence of distal colonic cancer in men increased by 14 per cent per decade (incidence rate ratio (IRR 1·14), 95 per cent c.i. 1·00 to 1·30; P = 0·042); the incidence of rectal cancer in men increased by 18 per cent (IRR 1·18, 1·06 to 1·32; P = 0·002) and that in women by 13 per cent (IRR 1·13, 1·02 to 1·26; P = 0·023). In those aged 50–79 years, there was a reduction in incidence per decade of proximal, distal and rectal cancers in both sexes. In the group aged 80 years and over, proximal cancer incidence per decade increased by 19 per cent in women (IRR 1·19, 1·13 to 1·26; P < 0·001) and by 25 per cent in men (IRR 1·25, 1·18 to 1·32; P < 0·001); among women, the incidence of distal colonic cancer decreased by 8 per cent (IRR 0·92, 0·86 to 0·98); P = 0·012), as did that of rectal cancer (IRR 0·92, 0·86 to 0·97; P = 0·005). Conclusion: The increasing incidence of rectal cancer among younger patients needs to be considered when implementing screening strategies. Abstract : Worrying trends in the under 50s